PRELIMINARY DESIGN OF A MOORING SYSTEM FOR 1 MWP FLOATING PHOTOVOLTAIC IN JATIGEDE RESERVOIR, WEST JAVA - Kristian P S, Pandu
The Government of Indonesia targets to achieve a share of 23% of the renewable energy mix by 2025 and 31% by 2050. National Energy General Plan (RUEN) states that solar power is one of the potential renewable energy sources in Indonesia, around 207,898 MW. However, the construction of Solar Photovoltaic is not easy, especially related to land availability. One of the solutions is to put solar panels on top of a body of water or known as Floating Photovoltaic (FPV). In this Final Project, a 1 MWp FPV is designed in Jatigede Reservoir, West Java specifically for the mooring system. The 1 MWp Floating PLTS consists of 10 separate floating structures each with a capacity of around 100 kWp. The layout of 1 structure has a length of 36.54 m and a width of 35.44 m consisting of 761 floaters with dimensions: 1260 mm × 400 mm × 215 mm and 336 solar modules with a capacity of 300 Wp. There are three mooring configurations designed and analyzed. In the first mooring configuration , the moorings are installed directly from the structure to the anchors. In the second mooring configuration, several moorings which connected to the structure are met at one point and connected by another mooring rope towards the anchor. The third configuration is the second configuration with buoys installed. Dynamic analysis was performed using the floating structure design and analysis software Orcaflex. Based on the output of the modeling, it is found that all three meet the design criteria for maximum tension and roll motion. The three configurations also meet the design criteria for maximum offset for water depth of 20 meters but the criteria are not met when the water depth is recedes to 18 meters.